Hydropolitics of conflict prevention: Effective transboundary freshwater resource management as a driver of peace - Huber,Johannes David (2022)
Global water scarcity is increasingly acknowledged as an issue of peace and security. Declining water availability as well as rising freshwater demand increase the likeliness of military action and violent conflicts over transboundary surface and underground freshwater resources. This thesis analyses whether riparian countries suffering from water scarcity are more prone to violent conflict and discusses how violence can be avoided by negotiating agreements and establishing resilient, independent and inclusive water management institutions. It further finds that cooperation instead of disputes over shared water resources is preferable despite strong context-specific challenges to successfully negotiate water management agreements. Furthermore, it offers a starting point for future research and aims at tentatively guiding water management policy.
Keywords: Hydropolitics; conflict prevention; water scarcity; water availability